Epidemiology of Monkeypox (Mpox) - Gómez-Benavides, Jorge Luis (2023)
Monkeypox was identified for the first time in captive monkeys in 1958, and later was identified in humans in 1970; this was a smallpox-like disease that was eradicated in 1980 and is considered a re-emerging infection disease. From being a zoonotic disease related to the habitat of its probable reservoirs in endemic countries of West and Central Africa, in may 2022, its spread was reported in non-endemic countries without any history of travel to Africa, predominantly affecting males with sexual behaviors risk (homosexuals, bisexuals and men who have sex with men). It should be implemented strategies aimed at reducing the contact rate and the reduction of susceptible subjects through specific vaccination.